NEGATIVE EMOTIONS AND TRAVEL DESIRE: EXPLORATION OF THE NEW NORMAL COVID-19 STAGE IN INDONESIA - Sari Lenggogeni (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
This study aims to explore domestic tourist emotions and their crisis behavioral intention during the stage of new normal phase associated to COVID-19 Pandemic. Using a purposive sampling, this study adopts quantitative exploratory with online survey technique in 34 provinces in Indonesia. A descriptive analysis was employed to explore tourist emotions underpinned by Russel’s emotion classification scheme and travel intention during the new normal a part of prodromal phase of COVID-19 crises lifecycle. About 3650 Indonesian “quarantined” resident- a former of active traveller before COVID-19 pandemic- participated in this study. This study found that being alerted, bored, exhausted as the top three main negative emotions developed during the new normal phase associated to COVID-19 pandemic. The result also showed most of tourist felt lack of tourist confidence to travel during the new normal phase. This study limited by single stage of prodromal phase in COVID-19 limited to Indonesian context. This study is one of the first that deeply explored tourist behavior centered on psychological factor in new normal phase- a transition phase between semi lockdown to normal era with COVID-19 health protocol in Tourism Disaster and Crisis Management discipline.